Biomarkers and clinical characteristics of autoimmune chronic spontaneous urticaria: Results of the PURIST Study. Issue 12 (29th July 2019) - Schoepke, Nicole; Asero, Riccardo; Ellrich, André; Ferrer, Marta; Gimenez‐Arnau, Ana; E. H. Grattan, Clive; Jakob, Thilo; Konstantinou, George N.; Raap, Ulrike; Skov, Per Stahl; Staubach, Petra; Kromminga, Arno; et al.
Abstract: Background: Autoimmune chronic spontaneous urticaria (aiCSU) is an important subtype of chronic spontaneous urticaria (CSU) in which functional IgG autoantibodies to IgE or its high‐affinity receptor (FcεRI) induces mast cell degranulation and subsequent symptom development. However, it has not been tightly characterized. This study aimed to better define the clinical and immunological features and to explore potential biomarkers of aiCSU. Methods: This was a multinational, multicenter study of 182 CSU patients. The clinical features studied included: urticaria activity and impact (UAS7 and quality of life); autologous serum skin test (ASST); IgG anti‐FcεRI and IgG anti‐IgE; IgG‐anti‐thyroperoxidase (IgG anti‐TPO); total serum IgE; and basophil reactivity (BASO) using the basophil activation test (BAT) and basophil histamine release assay (BHRA). Results: Of the 182 patients, 107 (59%) were ASST+, 46 (25%) were BASO+, and 105 (58%) were IgG anti‐FcεRI+/IgE+. Fifteen patients (8%) fulfilled all three criteria of aiCSU. aiCSU patients appeared more severe (UAS7 21 vs 9 P < 0.016) but showed no other clinical or demographic differences from non‐aiCSU patients. aiCSU patients also had markedly lower total IgE levels ( P < 0.0001) and higher IgG anti‐TPO levels ( P < 0.001). Of biomarkers, positive BAT and BHRA tests were 69% and 88% predictive of aiCSU, respectively. Conclusions: aiCSU is a relatively small but immunologically distinct subtype of CSU that cannot be identified by routine clinical parameters. Inclusion of BHRA or BAT in the diagnostic workup of CSU patients may aid identification of aiCSU patients, who may have a different prognosis and benefit from specific management. Abstract : Autoimmune chronic spontaneous urticaria (aiCSU) is defined by IgG anti‐IgE or FcεRI, a positive basophil activation test (BAT) and a positive autologous serum skin test (ASST). 14% of ASST+ patients have aiCSU with low IgE levels and elevated levels of anti‐thyroperoxidase. Positive BAT and basophil histamine release assays (BHRA) were 69% and 88% predictive of aiCSU and, therefore, are biomarkers.